Integrating Islamic social finance and community service to promote inclusive economic development - Jamludin, Nur; Tidjani, Shofiah; Suardi, Didi; Septi, Iti (Journal Ligundi of Community Service, 2025)
Background. The potential of Islamic social finance (ISF), which includes zakat, waqf, and sadaqah, extends beyond poverty alleviation and has increasingly been recognized as a catalyst for inclusive and sustainable economic development. However, the effectiveness of ISF initiatives largely depends on their integration with community service programs that ensure local participation, empowerment, and social inclusion. Despite its relevance, there is limited empirical evidence on how structured collaborations between ISF institutions and community-based services contribute to inclusive growth. Purpose. This quantitative study aimed to examine the role of integrating Islamic social finance and community service in promoting inclusive economic development. Specifically, it explored whether the outcomes of such integration are influenced by four key factors: community participation, financial literacy, institutional governance, and technology adoption. Method. The study involved 288 beneficiaries and stakeholders from zakat and waqf-based community programs across three regions in Indonesia. Data were collected through structured questionnaires and analyzed using statistical methods, including multiple regression and structural equation modeling (SEM). Results. The findings reveal that programs combining Islamic social finance with community service significantly enhance local economic inclusivity through entrepreneurship development, skills training, and microfinance support. Moreover, community participation and financial literacy emerged as strong predictors of positive outcomes, while weak institutional governance reduced the overall impact of such initiatives. Conclusion. This study highlights the importance of integrating ISF and community service to foster equitable and inclusive economic growth. It provides actionable insights for policymakers and practitioners to strengthen collaborative models, enhance governance, and utilize technology in managing Islamic social finance initiatives for sustainable community development.